Penyuluhan Pra Nikah Bagi Pemuda Dan Remaja Masjid Di Desa Pulau Pule Kecamatan Air Batu - Zaleha, Syawaluddin, Aminudin (Center of Knowledge : Jurnal Pendidikan Dan Pengabdian Masyarakat, 2023)
Through Counseling on the socialization of premarital seminars for youth and mosque youth in Pulau Pule Village in Air Batu District, Asahan Regency. Islam regulates how to choose an ideal partner who can understand the rights and obligations of each after getting married. The phenomenon that often occurs with an increase in divorce in the regions is a sign of the unpreparedness of husband and wife for their rights and obligations in carrying out their duties. Counseling on pre-marital preparation from the perspective of Islamic law is carried out to increase knowledge about families who are kinah, mawaddah wa rahmah so that they can prepare them to choose a life partner and assume responsibility in marriage. This counseling provides interesting materials such as the concept of choosing a life partner, the process of ta'ruf and khitbah, and the rights and obligations of husband and wife, and also prepares pious offspring from Islamic provisions and psychology. both men and women. The results of the counseling indicated that there was an increase in the participants' knowledge regarding pre-marital preparation from the perspective of Islamic law.